Molecular dynamics model of mechanophore sensors for biological force measurement - Sumit Mittal; Rongsheng E. Wang; Robert Ros; Alison E. Ondrus; Abhishek Singharoy (Heliyon)
Cellular forces regulate an untold spectrum of living processes, such as cell migration, gene expression, and ion conduction. However, a quantitative description of mechanical control remains elusive due to the lack of general, live-cell tools to measure discrete forces between biomolecules. Here we introduce a computational pipeline for force measurement that leverages well-defined, tunable release of a mechanically activated small molecule fluorophore. These sensors are characterized using a multiscale approach combining equilibrium and steered QM/MM molecular dynamics models to capture the chemical, mechanical, and conformational transitions underlying force activation thresholds on a nano Newton scale. We find that chemical modification of the mechanophore and variation of its biomolecular tethers can tune the rate-determining step for fluorophore release and adjust the mechanochemical activation barrier. The models offer a new molecular framework for calibrated, programmable biomolecular force reporting within the live-cell regime, opening new opportunities to study mechanical phenomena in biological systems.